2004
DOI: 10.1046/j.1365-2672.2003.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of novel beta-ribosidase substrates for the differentiation of Gram-negative bacteria

Abstract: Aims: To synthesize novel substrates for the detection of b-ribosidase and assess their potential for the differentiation of Gram-negative bacteria. Methods and Results: Two novel chromogenic substrates, 3¢,4¢-dihydroxyflavone-4¢-b-D-ribofuranoside (DHFriboside) and 5-bromo-4-chloro-3-indolyl-b-D-ribofuranoside (X-riboside) were evaluated along with a known fluorogenic substrate, 4-methylumbelliferyl-b-D-ribofuranoside (4MU-riboside). A total of 543 Gram-negative bacilli were cultured on media containing eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Hence, E. vulneris did not produce the fluorescent colonies on media as negative reaction [19]. Since Butterworth et al [21] reported that the difference of β-ribosidase activity was due to different rates of substrate uptake through the cell envelop or differences in the substrate affinity of the β-ribosidase enzyme within different species.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, E. vulneris did not produce the fluorescent colonies on media as negative reaction [19]. Since Butterworth et al [21] reported that the difference of β-ribosidase activity was due to different rates of substrate uptake through the cell envelop or differences in the substrate affinity of the β-ribosidase enzyme within different species.…”
Section: Discussionmentioning
confidence: 99%
“…Other chelation‐based substrates applicable to agar media include those based on alizarin and 3′, 4′‐dihydroxyflavone although these have not yet been applied in commercially available chromogenic media (James et al. 2000; Butterworth et al. 2004).…”
Section: Chromogenic Substratesmentioning
confidence: 99%
“…2007). The development of new media may depend upon the recognition and synthesis of new chromogenic substrates with diagnostic utility (Butterworth et al. 2004).…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
“…The β-ribosidase inhibitory properties of 6 − 8 were evaluated using 3‘,4‘-dihydroxyflavone-4‘-β- d -ribofuranoside 16 (DHF-riboside) as the substrate and bacterial lysates or whole cells as the source of β-ribosidase. The hydrolysis of this chromogenic substrate can be catalyzed by β-ribosidases to release 3‘,4‘-dihydroxyflavone, which forms a highly colored chelate with iron …”
mentioning
confidence: 99%